De volta para os braços da rainha dos céus: migração, memória e festa em Caicó/RN - Pereira, Carlos Eduardo de Brito (2011)
The present work has as an objective to seize up some particular meanings of the Feast of Sant Ana (The saint which represents the city of Caicó/RN), a central event of the calendar festive-religious of that city, looking for to perceive on how it combines with the symbolic poles sacred: profane through the social bonds that are present there performed and expressed through the social networking and of local belongings. Such bond ties reveal themselves through a very especial manner, through the migration of returning to the feast, when collectively are produced and updated knowledge and codes that reinforce the representation of the local belonging, nominated as being caicoense . We seek on perceiving how the many events of this feast (from a perspective of a religious order as well as laic) acting on a conclusive way to an identity of the re-meaning of that city, especially in its relation with the migrant natives: the sons and daughters that return to the arms of Sant Ana